Enhancement of Viola-Jones Algorithm using Local Binary Pattern Applied to Face Detection - Jasmine Anetin; Dominique Kyle Gonzaga; Vanessa Mae Castillon; Vivien A Agustin (International Journal on Orange Technologies, 2022)
Face detection is a type of computer image processing technology that can detect faces in digital images. In real-time applications such as CCTV surveillance and video tracking, automatic face detection and recognition is the most difficult and rapidly increasing study topic. One of the most well-known and often used methods for detecting human faces is the Viola-Jones Algorithm. The difficulty associated with the algorithm can be attributed to many variations in the angles of a person's face. In this paper, an enhanced Viola-Jones algorithm with a local binary pattern (LBP) is used to recognize numerous and tilted faces with excellent accuracy.